Molecular cloning and three‐dimensional structure prediction of a novel α‐tubulin in Caenorhabditis elegans - Baleanu‐Gogonea, Camelia (Blackwell Publishing Ltd, 2007)

(untitled) (J Cell Mol Med)
This paper reports on the isolation of a cDNA clone (tba‐6) encoded by a novel a‐tubulin gene in the nematode C. elegans. The tba‐6 gene is located on chromosome I, that encode a protein of 460 amino acids, as well as the expression of the gene during the development. Here we discuss the structure of the coding region and the regulatory sequences in the promoter region. The comparison of the amino acid sequence of TBA6 with other α‐tubulin isotypes of C. elegans, suggests that these proteins are highly conserved in most of the N‐terminal and intermediate sequence, but they have highly divergent C‐terminal sequences. TBA6 has also high homology with other α‐tubulin families (e.g. human, mouse, Drosophila melangaster). The in situ experiment results suggest that the tba‐6α‐tubulin gene is required during the entire embryonic development, therefore it is required during the early cell division stages. Further, we determined the 3D structure of C. elegans TBA6 α‐tubulin by altering (computationally) the crystal structure of the α‐tubulin (TBA_pig) from porcine α‐β tubulin dimer. We discuss structural conservation and changes in the pattern of interactions between secondary structure elements of TBA_pig and TBA6, respectively.